Moderasi Beragama Untuk Gen Z Antara Nilai, Narasi dan Aksi Nyata - Syaidun; Nuryuhefi , Endis (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This study aims to explore how religious moderation values are internalized, narrated, and transformed into real actions among Generation Z students in MA Syarifatul Ulum Ngawi. Given the unique characteristics of Gen-Z digitally native, socially dynamic, and information-critical conventional approaches are insufficient in building moderate religious attitudes. This research employs a qualitative descriptive method using in-depth interviews, participatory observation, and documentation. The focus is to understand students' perceptions, experiences, and expressions related to religious moderation values and practices within school and digital contexts. The study finds that religious moderation becomes effective only when transformed from abstract values into personal narratives and participatory actions. Through storytelling, reflective dialogue, and active engagement in interfaith collaboration and social diversity projects, students are more likely to experience and embody the values of tolerance, justice, balance, and anti-violence in their daily lives. This study is context-specific to one Islamic senior high school and may not fully represent broader educational settings. However, it provides useful insights for developing value-based education frameworks tailored for Gen-Z characteristics. This study contributes to the discourse on religious moderation by emphasizing the integration of value internalization, narrative construction, and real-life action. It highlights the strategic role of schools in shaping moderate and tolerant identities in the digital age through experiential and media-based learning. Keywords: Religious moderation, Generation Z, Narrative based education, Value internalization, Inclusive education